2021
DOI: 10.1016/j.intell.2021.101526
|View full text |Cite
|
Sign up to set email alerts
|

Age-related nuances in knowledge assessment

Abstract: We have no conflicts of interests to disclose. We confirm that the work conforms to Standard 8 of the American Psychological Association's Ethical Principles of Psychologists and Code of Conduct. We thank Diana Steger for developing the large item pool that we partially used in this study and Johannes Zimmermann for his helpful comments on an earlier draft of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 78 publications
4
29
0
2
Order By: Relevance
“…For declarative knowledge, the breadth and depth of the assessment hinges on the compilation of item sets. Thus, item sampling issues are even more pressing and crucial than for other psychological constructs (Cattell, 1987; Schroeders et al, 2021; Schroeders, Wilhelm, et al, 2016; Steger et al, 2019). Some of the domains are part of school curricula, for example, for the domains of the natural sciences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For declarative knowledge, the breadth and depth of the assessment hinges on the compilation of item sets. Thus, item sampling issues are even more pressing and crucial than for other psychological constructs (Cattell, 1987; Schroeders et al, 2021; Schroeders, Wilhelm, et al, 2016; Steger et al, 2019). Some of the domains are part of school curricula, for example, for the domains of the natural sciences.…”
Section: Discussionmentioning
confidence: 99%
“…To infer from the content of an item to the opportunity or context at which the content is learned is fuzzy and opaque. For instance, although there are age-related differences in the solution probabilities for specific items, there is no convincing classification of items based on such information (Schroeders et al, 2021). Second, regarding a separation of general and specialized knowledge, recent research based on very broad item samples suggested that even large numbers of highly heterogeneous knowledge domains can be described satisfactorily with a strong general factor in a hierarchical model (Schipolowski et al, 2014; Steger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations